2013
DOI: 10.1016/j.midw.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with nutrition-related information during antenatal care of pregnant women of different ethnic backgrounds residing in the area of Oslo, Norway

Abstract: the midwife is considered a trustworthy source of nutrition-related information. Therefore, antenatal care may have considerable potential to promote a healthy diet to pregnant women. Findings suggest that nutrition communication in antenatal care should be more tailored towards women's dietary habits and cultural background, nutritional knowledge as well as level of nutrition literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
102
2
6

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(124 citation statements)
references
References 47 publications
14
102
2
6
Order By: Relevance
“…In addition, given the rapid increase in available apps to manage GDM [38], participants in our study outlined that it was important that they could trust the developer and information in the app. This finding is in line with another qualitative study among pregnant women in Norway, were information from health professional was the most trustworthy source of health-related information [15].…”
Section: Discussion Principal Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, given the rapid increase in available apps to manage GDM [38], participants in our study outlined that it was important that they could trust the developer and information in the app. This finding is in line with another qualitative study among pregnant women in Norway, were information from health professional was the most trustworthy source of health-related information [15].…”
Section: Discussion Principal Resultssupporting
confidence: 90%
“…However, they often felt that women had difficulties to remember all the information. This is in line with other studies reporting an information overload among pregnant women [15,36]. Similarly, a pilot test of an app to monitor gestational weight gain found that it could help pregnant women to cope with the great amount of information provided by different sources [37].…”
Section: Discussion Principal Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Una de las principales carencias percibidas por las gestantes fue recibir consejos escasos y centrados en temas de seguridad alimentaria (24), así como orientaciones poco específicas o aportadas en un momento demasiado avanzado de la gestación (18,26), cuando los intereses de las gestantes están ya más centrados en otros aspectos como la salud del feto (22). A pesar de ello, la figura de la matrona en cuanto a la información nutricional es tenida muy en cuenta por las gestantes, debido a la especial vinculación que mantienen y por la experiencia que se le atribuye (23). Por otra parte, las matronas son conscientes de la importancia de su labor en el asesoramiento nutricional y de que el embarazo es un momento especialmente favorable para intervenir en esta cuestión (18), pero existen importantes diferencias entre ellas en función de su ámbito geográfico de procedencia.…”
Section: Discussionunclassified
“…Por otra parte, las matronas son conscientes de la importancia de su labor en el asesoramiento nutricional y de que el embarazo es un momento especialmente favorable para intervenir en esta cuestión (18), pero existen importantes diferencias entre ellas en función de su ámbito geográfico de procedencia. Mientras que las matronas británicas se sienten más inseguras y dudan de la eficacia de sus estrategias concretas de consejo dietético (23,29), las matronas neozelandesas (17) y canadienses (21) sienten que dominan mucho más el asesoramiento nutricional. En cuanto a las técnicas usadas por las matronas a la hora de aconsejar medidas nutricionales a las gestantes se han identificado: la repetición de mensajes nutricionales, la eliminación de algún producto concreto de la dieta, los acuerdos con las parejas, y la exposición de riesgos médicos y obstétricos de un patrón alimentario inadecuado (23).…”
Section: Discussionunclassified